Respuesta :
Answer:
[tex]\large\boxed{\cos\theta=\pm\dfrac{2}{3}}[/tex]
Step-by-step explanation:
Use [tex]\sin^2x+\cos^2x=1[/tex].
We have
[tex]\sin\theta=\dfrac{\sqrt5}{3}[/tex]
Substitute:
[tex]\left(\dfrac{\sqrt5}{3}\right)^2+\cos^2\theta=1\qquad\text{use}\ \left(\dfrac{a}{b}\right)^n=\dfrac{a^n}{b^n}\\\\\dfrac{(\sqrt5)^2}{3^2}+\cos^2\theta=1\qquad\text{use}\ (\sqrt{a})^2=a\\\\\dfrac{5}{9}+\cos^2\theta=1\qquad\text{subtract}\ \dfrac{5}{9}\ \text{from both sides}\\\\\cos^2\theta=\dfrac{9}{9}-\dfrac{5}{9}\\\\\cos^2\theta=\dfrac{4}{9}\to \cos\theta=\pm\sqrt{\dfrac{4}{9}}\\\\\cos\theta=\pm\dfrac{\sqrt4}{\sqrt9}\\\\\cos\theta=\pm\dfrac{2}{3}[/tex]
Answer: [tex]cos(\theta)=\±\frac{2}{3}[/tex]
Step-by-step explanation:
In this case we know that:
[tex]sin(\theta) = \frac{\sqrt{5}}{3}[/tex]
To find the value of [tex]cos(\theta)[/tex] we use the following trigonometric identity
[tex]cos^2(\theta)=1-sin^2(\theta)[/tex]
So
[tex]sin^2(\theta) = (\frac{\sqrt{5}}{3})^2[/tex]
Therefore
[tex]cos^2(\theta)=1-(\frac{\sqrt{5}}{3})^2[/tex]
[tex]cos^2(\theta)=1-\frac{5}{9}[/tex]
[tex]cos^2(\theta)=\frac{4}{9}[/tex]
[tex]cos(\theta)=\±\sqrt{\frac{4}{9}}[/tex]
[tex]cos(\theta)=\±\frac{2}{3}[/tex]